Cold Shock Response of Bacillus subtilis: Isoleucine-Dependent Switch in the Fatty Acid Branching Pattern for Membrane Adaptation to Low Temperatures - Klein, Wolfgang (American Society for Microbiology (ASM), 1999)
Bacillus subtilis has developed sophisticated mechanisms to withstand fluctuations in temperature. Membrane fatty acids are the major determinants for a sufficiently fluid membrane state to ensure the membrane’s function at all temperatures. The fatty acid profile of B. subtilis is characterized by a high content of branched fatty acids irrespective of the growth medium. Here, we report on the importance of isoleucine for B. subtilis to survive cold shock from 37 to 15°C. Cold shock experiments with strain JH642 revealed a cold-protective function for all intermediates of anteiso-branched fatty acid biosynthesis. Metabolites related to iso-branched or straight-chain fatty acid biosynthesis were not protective. Fatty acid profiles of different B. subtilis wild-type strains proved the altered branching pattern by an increase in the anteiso-branched fatty acid content and a concomitant decrease of iso-branched species during cold shock. There were no significant changes in the fatty acid saturation or acyl chain length. The cold-sensitive phenotype of isoleucine-deficient strains in the absence of isoleucine correlated with their inability to synthesize more anteiso-branched fatty acids, as shown by the fatty acid profile. The switch to a fatty acid profile dominated by anteiso-C(15:0) and C(17:0) at low temperatures and the cold-sensitive phenotype of isoleucine-deficient strains in the absence of isoleucine focused our attention on the critical role of anteiso-branched fatty acids in the growth of B. subtilis in the cold.